1979
DOI: 10.1093/nar/6.7.2453
|View full text |Cite
|
Sign up to set email alerts
|

A ribonuclease-resistant region of 5S RNA and its relation to the RNA binding sites of proteins L18 and L25

Abstract: An RNA fragment, constituting three subfragments of nucleotide sequences 1-11, 69-87 and 89-120, is the most ribonucleaseresistant part of the native 5S RNA of Escherichia coli, at 0°C. A smaller fragment of nucleotide sequence 69-87 and 90-110 is ribonuclease-resistant at 250.Degradation of the L25-5S RNA complex with ribonuclease A or T2 yielded RNA fragments similar to those of the free 5S RNA at 0°C and 25°C; moreover L25 remained strongly bound to both RNA fragments and also produced some opening of the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 29 publications
7
52
1
Order By: Relevance
“…Because a-sarcin is pyrimidine blind, we cannot determine whether they are part of the L25 binding site. However, nuclease protection experiments have indicated that three of the pyrimidines (bases 87-89) remain sensitive in the presence of L25 (28,29). Thus, our definition of the L25 binding site on 5S rRNA (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because a-sarcin is pyrimidine blind, we cannot determine whether they are part of the L25 binding site. However, nuclease protection experiments have indicated that three of the pyrimidines (bases 87-89) remain sensitive in the presence of L25 (28,29). Thus, our definition of the L25 binding site on 5S rRNA (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…A fragment derived from 5S rRNA by limited nuclease digestion and containing the sequences 69-87 and 90-110 binds L25 specfically and with high affinity (28). In addition, the guanosine-81 and cytosine-93 residues are protected from cleavage by the double-strand-specific cobra venom endonuclease on addition of L25 to 5S rRNA (29), further implicating helix IV as part of the binding site.…”
Section: Discussionmentioning
confidence: 96%
“…L18 (26). Protein L25, on the other hand, appear to assemble relatively independently of L18; it has a separate binding sites on the 5S RNA (15,17) and, apparently, induces independent changes in the 5S RNA structure (7,15,17).…”
Section: Methodsmentioning
confidence: 99%
“…With the completion of the sequencing project in Bacillus subtilis, it became clear that the genes for several of the key enzymes involved in RNA maturation and decay in Escherichia coli are absent from its Grampositive counterpart+ Neither the RNase E gene, rne, nor that of oligoribonuclease, orn, both essential for E. coli viability (Apirion & Lassar, 1978;Ono & Kuwano, 1979;Ghosh & Deutscher, 1999), is present in B. subtilis+ Also missing are the genes encoding a battery of exonucleases involved in tRNA maturation, namely RNase T, RNase BN, and RNase D (Li & Deutscher, 1994)+ RNase E is a key enzyme of RNA metabolism in E. coli (Ono & Kuwano, 1979)+ It is responsible for the initial rate-limiting cleavage in the decay of many mRNAs (reviewed in Grunberg-Manago, 1999), as well as playing an important role in 16S and 5S ribosomal RNA processing (Ghora & Apirion, 1978;Li et al+, 1999)+ In 1974, Pace and coworkers described a ribosomeassociated activity called RNase M5, responsible for 5S rRNA maturation in B. subtilis (Sogin & Pace, 1974)+ We therefore wondered whether this enzyme could fulfill an RNase E-like role in B. subtilis and undertook to repurify this activity and identify the gene responsible+ The enzyme that Pace described had a molecular weight of about 24 kDa on SDS-polyacrylamide gels (Pace et al+, 1984)+ It required a protein cofactor, identified as ribosomal protein L18 (called BL16 at the time), for pre-5S to 5S maturation (Stahl et al+, 1984)+ The function provided by L18, one of three proteins known to bind 5S rRNA in E. coli, along with L25 and L5 (Gray et al+, 1972;Douthwaite et al+, 1979;Egebjerg et al+, 1989; Fig+ 1), can be replaced by addition of 25% DMSO+ Thus, L18 is thought to ensure the correct conformation of the substrate for processing, rather than playing a direct role in the cleavage reaction itself (Pace et al+, 1984)+ B. subtilis L18 can also be replaced by its E. coli counterpart (Stahl et al+, 1984)+ L5, which binds to the 5S processing stalk, inhibits the cleavage reaction at high concentrations (Stahl et al+, 1984)+ RNase M5 cleaves the 5S precursor in a doublestranded region that extends from the L5 arm (Fig+ 1)+ The specificity determinants of the cleavage reaction were well characterized by Pace+ Although the natural substrate is double-stranded for three further nucleotides beyond the 39 end of the mature 5S rRNA, it was shown that base pairing of the 39-terminal residue was sufficient for cleavage to occur Stahl et al+, 1980)+ Although this residue is naturally a cytosine in B. subtilis, cleavage still occurred when it was replaced by any of the other 3 nt, provided b...…”
Section: Introductionmentioning
confidence: 99%